La legitimación en el proceso civil peruano - Prado Bringas, Rafael (2018)
The objective of this article is to define the legitimacy of the process, as well as to understand the different types of legitimation that have been defined in the doctrine and, consequently, adopted in the Peruvian civil process. Also, it seeks to analyze how the control of this budget should be in the process. It does not intend to settle a controversy, but only to expose our ideas, and try to give this procedural budget a practical purpose, from a reading of it from the Constitution and the general theory of the process.